Toxicity testing for oncology drugs - Reynolds, Theresa; Allamneni, Krishna (Henry Stewart Talks, 2009)
Special considerations for the development of oncology drugs and impact on design of toxicology programs, Key similarities and differences in small molecule and large molecule toxicology programs, Value of PD marker in drug development, Current regulatory guidance for oncology products
Archived at 2024/02/29